The role of endoscopic retrograde pancreatography in the management of pancreatic trauma - Thomson, David Alexander (Department of Surgery, 2015)
Background: Endoscopic retrograde pancreatography (ERP) has various applications in the diagnosis and management of pancreatic trauma. The utility of ERP in pancreatic trauma presenting to a level 1 equivalent trauma centre was analysed. Methods: Patients who sustained pancreatic trauma and underwent ERP were identified. Patient demographics, mechanism of injury, time to presentation, diagnostic modalities, associated injuries, clinical management, endoscopic interventions and their timing, surgical treatment and patient outcomes were recorded. Results: Forty-eight patients with pancreatic trauma were referred for ERP after blunt (26), gunshot (15), or stab (7) injury. The average time from injury to ERP was 38 days (range 2 – 365). An ERP visualized the duct in 47 patients. Twenty-four patients had a pancreatic fistula, 12 patients had a main pancreatic duct stricture or cut-off and 10 patients had a pseudocyst. Endoscopic interventions were pancreatic duct sphincterotomy (15), pancreatic duct stent (7) or pseudocyst drainage (6). Ten patients demonstrated minor injuries and no interventions were performed. One patient had a normal pancreatogram. Ten patients required pancreatic surgery following ERP (distal pancreatectomy n=6, pancreaticojejenostomy n=3 and cystjejenostomy n=1). One patient unable to tolerate ERP had a distal pancreatectomy. Conclusion: The majority of ERPs were performed post surgery or after a delayed presentation. Diagnostic success was high and in conjunction with therapeutic interventions 77% of patients avoided surgery for their pancreatic complications. ERP is an effective tool in the delayed management of the local complications of pancreatic trauma.